The Attribute in the Boreal Images on the Celestial Medieval Planispheres - Sayáns Gómez, Francisco (Eikón / Imago, 2019)
The attribute has always something to tell about the object or image that it qualifies. In some cases, its only presence is enough to evocate it. Of all the images that populate a manuscript and the medieval celestial planispheres, some show attributes that are specific to them. This work studies and analyzes iconologicaly, as of the original sources, the essence of the attributes that illustrate the boreal images that they stand for. This is what marks the iconological importance of its presence in the manuscripts and medieval planispheres as sources of information.